Pengaruh Fitur Live Streaming dan Content Marketing terhadap Keputusan Pembelian Konsumen pada Tiktok Shop - Raihan Raihan; Yusrawati Yusrawati; Al Mahfud Saputra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of live streaming features and content marketing on consumer purchasing decisions on TikTok Shop, focusing on students of Universitas Almuslim. This study employed a quantitative approach with an associative research design. The population consisted of Universitas Almuslim students, while the sample included 96 respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS. The results show that, partially, the live streaming feature has a positive and significant effect on purchasing decisions, with a significance value of 0.024. Furthermore, content marketing also has a positive and significant effect on purchasing decisions, with a significance value of 0.003. Simultaneously, live streaming and content marketing have a significant effect on purchasing decisions, with a significance value of 0.000. The coefficient of determination (R²) of 0.270 indicates that both independent variables explain 27.0% of the variance in purchasing decisions, while the remaining 73.0% is influenced by other factors outside the research model. These findings confirm that consumer purchasing decisions on TikTok Shop are influenced by the quality of digital content and interactive marketing communication.